2017
DOI: 10.1016/j.neuron.2017.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal Cell-Interneuron Circuit Architecture and Dynamics in Hippocampal Networks

Abstract: Summary Excitatory control of inhibitory neurons is poorly understood due to the difficulty of studying synaptic connectivity in vivo. We inferred such connectivity through analysis of spike timing and validated this inference using juxtacellular and optogenetic control of presynaptic spikes in behaving mice. We observed that neighboring CA1 neurons had stronger connections, and that superficial pyramidal cells projected more to deep interneurons. Connection probability and strength were skewed, with a minorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
304
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 224 publications
(355 citation statements)
references
References 77 publications
(106 reference statements)
10
304
0
Order By: Relevance
“…Next, we quantified the relationship between neuronal spiking and LFP in the gRSC. We isolated single units, which were classified as putative pyramidal neurons or interneurons 35 (Supplementary Fig. 2).…”
Section: Transient Ripple (140-200 Hz) Oscillations In the Grscmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we quantified the relationship between neuronal spiking and LFP in the gRSC. We isolated single units, which were classified as putative pyramidal neurons or interneurons 35 (Supplementary Fig. 2).…”
Section: Transient Ripple (140-200 Hz) Oscillations In the Grscmentioning
confidence: 99%
“…Units with firing rate < 0.5 Hz or ISI violation > 0.01 were discarded. Units were separated into putative pyramids and interneurons based on the spike width, waveform asymmetry and firingrate using k-means 35 .…”
Section: Histological Processingmentioning
confidence: 99%
“…We hypothesized that the changes in SWR participation of synaptically activated interneurons and the place field remapping, particularly of non-stimulated cells, was due to a reorganization of lateral inhibition. To explore this hypothesis, we examined spike transmission between pairs of monosynaptically connected pyramidal cells and interneurons (PYR-INT) 18 Methods) to measure changes in the influence of the presynaptic drive to the postsynaptic interneuron while regressing out changes in postsynaptic firing rate ( Figure 4A; Figure S4). We found that putative synaptic coupling strength, as approximated by our spike transmission measure, varied 64.7±0.5% around the mean over the recording session ( Figure 4A,B, Figure S4).…”
mentioning
confidence: 99%
“…Modeling and experiments in-vitro suggest that pyramidal cells are more susceptible to polarization than are symmetrical interneurons 27,28 , so we tested whether this was evident in-vivo. We used the width of extracellularly recorded action potentials to segregate putative pyramidal neurons from non-pyramidal neurons, a common analysis that was recently validated by cell-type specific optogenetic stimulation 40 for these broad classes of neurons (but has limitations 41 ). Figure 3a shows that the distribution of spike waveform width is bimodal, and the average spike shape of each cluster (pyramidal "RS" cells: ≥250µs, N=1812) and blue (non-pyramidal "FS" cells: <250µs, N=859).…”
Section: Direction Of Modulation Depends On Cell Typementioning
confidence: 99%
“…Comparison between tDCS and Sham experiments were made using independent t-tests. The number of neurons N varied from session to session and we discarded any session with N<10 (experiments included; Monkey S: 59, Monkey W: 40), with N ranging from 10 to 54 with median of 27. Results for both monkeys were similar, and we combined experiments to increase power for statistical analysis.…”
Section: Neural Population Dynamics Dimensionality Reduction and Analmentioning
confidence: 99%